Are American Cultural Examples Losing the International Students in U.S. Classrooms?. (September 2016) - Priya, Kanu; Tapis, Gregory P.
This article illustrates techniques that can help instructors overcome the challenges of a much overlooked teaching element—that of using examples while teaching management in a multicultural classroom filled with both domestic and international students. We provide suggestions for steps that instructors can take to improve their content delivery for an international classroom without compromising their current use of pedagogical tools such as examples, storytelling, and active learning exercises.